Концепт Arrogance в британській картині світу - Єфимчук, Галина Олегівна; Yefymchuk, H. O. (Східноєвропейський національний університет імені Лесі Українки, 2014)
У пропонованій розвідці концепт ARROGANCE розглянуто як елемент британської національної картини світу, визначено його місце та роль у сучасному світосприйнятті британців. У ході дослідження наведено основні номінанти концепту; окреслено репрезентацію концепту на лексико-фразеологічному рівні; схаракте¬ризовано особливості вербалізації концепту у творах англійської літератури. Зроблено висновки щодо подаль¬ших перспектив вивчення концепту ARROGANCE. In this article the concept ARROGANCE is considered as an element of British national picture of the world. The British mentality and social factors that have influenced its development and formation have been analyzed. Isolated geographical position and the preservation of strict social stratification are considered to be the main factors which determined peculiar British mentality. That is also the origin of British arrogance towards other nations. Thus, concept ARROGANCE has been identified as one of the main elements of the British picture of the world in both past and present days. The article describes the basic nominative means of the concept, outlines the verbalization of the concept on the lexical and phraseological level. The article includes examples of representation of the concept ARROGANCE in the works of English literature. Based on the research conclusions have been made regarding the future prospects of studying the concept ARROGANCE.
Concept Arrogance in British Picture of the World
Keywords: лексико-фразеологічні засоби; lexical and phraseological means; концепт; concept; картина світу; world picture